Developing and sustaining specialist and advanced practice roles in nursing and midwifery: A discourse on enablers and barriers. Issue 19 (23rd July 2018) - Fealy, Gerard M; Casey, Mary; O'Leary, Denise F; McNamara, Martin S; O'Brien, Denise; O'Connor, Laserina; Smith, Rita; Stokes, Diarmuid
Abstract : Aims and objectives: To collate, synthesise and discuss published evidence and expert professional opinion on enablers and barriers to the development and sustainability of specialist and advanced practice roles in nursing and midwifery. Background: Expanded practice is a response to population health needs, healthcare costs and practitioners' willingness to expand their scope of practice through enhanced responsibility, accountability and professional autonomy. Design: This discursive paper is based on a rapid review of literature on enablers and barriers to the development and sustainability of specialist and advanced practice roles and is part of a wider policy analysis. Methods: We analysed and synthesised of 36 research articles, reviews and discussion papers on enablers and barriers in the development and sustainability of expanded practice roles. Results: Several factors enable role expansion, including: role clarity; credentialing and endorsement; availability of education for expanded roles; individual practitioners' dispositions towards role expansion; support from peers, other professionals and the work organisation; and costs. Where limited or absent, these same factors can constrain role expansion. Conclusions: Enabling nurses and midwives to practice to their full scope of education and expertise is a global challenge for disciplinary leadership, a national challenge for professional regulation and a local challenge for employers and individual clinicians. These challenges need to be addressed through multistakeholder coordinated efforts at these four levels. Relevance to clinical practice: This discursive paper synthesises empirical evidence and expert professional opinion on the factors that enable or hinder the development and sustainability of specialist and advanced practice roles. Providing a critical appraisal of current knowledge, it provides a reference source for disciplinary debate and policy development regarding the nursing and midwifery resource and informs clinicians of the myriad issues that can impact on their capacity to expand their scope of practice.